2022
DOI: 10.1088/1748-0221/17/02/p02025
|View full text |Cite
|
Sign up to set email alerts
|

Design of a high-resolution Rayleigh-Taylor experiment with the Crystal Backlighter Imager on the National Ignition Facility

Abstract: The Rayleigh-Taylor (RT) instability affects a vast range of High Energy Density (HED) length scales, spanning from supernova explosions (1013 m) to inertial confinement fusion (10-6 m). In inertial confinement fusion, the RT instability is known to induce mixing or turbulent transition, which in turn cools the hot spot and hinders ignition. The fine-scale features of the RT instability, which are difficult to image in HED physics, may help determine if the system is mixing or is transitioning … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, thanks to the recent technological progresses, these measurement techniques allowed a detailed characterisation of both medium and flow also at small scales. Some examples are the X-ray synchrotron microtomography [ 130 ], with resolution in space of 3.25 m and in time of 6 s. Recent experiments [ 131 , 132 ] have shown that the resolution can be further lowered down to 2.3 m, with a technique also allowing for higher resolution in time. At the time being, similar performances are also achieved by commercial micro-CT systems.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…However, thanks to the recent technological progresses, these measurement techniques allowed a detailed characterisation of both medium and flow also at small scales. Some examples are the X-ray synchrotron microtomography [ 130 ], with resolution in space of 3.25 m and in time of 6 s. Recent experiments [ 131 , 132 ] have shown that the resolution can be further lowered down to 2.3 m, with a technique also allowing for higher resolution in time. At the time being, similar performances are also achieved by commercial micro-CT systems.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…In contrast, many other simulations required the onset of the RTI to be at lower wavenumbers due to numerical reasons. The issue of numerical and experimental space-time resolution has been explained in [29], highlighting the improved experimental capabilities in recent times while discussing the parameter ranges of the Liepmann-Taylor scale also in the context of the design of capsules for inertial confinement fusion [30]. The fuel mixture is bombarded by a laser for the initiation process of fusion.…”
Section: Introductionmentioning
confidence: 99%
“…We have already noted that high accuracy compact schemes used for solving compressible NSE without the Stokes' hypothesis enable one to track the onset of RTI to be from the edges and corners of the interface [14,20,21] for 2D RTI problem. The authors in [29] used a 2D multi-physics simulation package, HYDRA [31,32] with a spatial resolution of the order of 3µm and time steps of the order of 100ps. It was noted that for the nuclear fusion experiments using radiography, the ideal spacetime resolution should be of the order of 2µm and 0ps to capture the evolving spikes!…”
Section: Introductionmentioning
confidence: 99%
“…RT turbulence can be observed in oceanographic and atmospheric flows ( 2 ), astrophysics ( 3 , 4 ) and in industrial settings such as combustion chambers ( 5 ). RT turbulence also occurs in all types of nuclear fusion ( 6 8 ), where it represents the main limiting factor to achieve functional inertial confinement fusion reactors ( 9 , 10 ).…”
mentioning
confidence: 99%